"Living Ghosts" and how to "Cook" Them: Homo Sacer as a "Sociodicy of (Im)purity" among the Miao of Guizhou, China. Issue 3 (2nd July 2020) - Liu, Yan; Tan, Chris K. K.
ABSTRACT: Agamben (1998) famously resurrected the homo sacer figure from obscurity in ancient Roman law. Originally conceived as a heuristic device, this "sacred man" concept has been applied largely in studies of refugees and prisoners. This article makes use of the concept in the more traditionally anthropological arenas of kinship and marriage. Some Miao in China's Guizhou province have been branded as "living ghosts", because their ancestors allegedly betrayed their village to pillaging rebels. We argue that this branding might have reflected not so much the betrayal, but rather longstanding socioeconomic and political tensions between the Miao and neighbouring ethnic groups. As such, we regard the living ghosts' origin story more as a social justification of ontological (un)cleanliness that we call "sociodicy of (im)purity". Lastly, the ghosts' collective wealth and political influence prevent their complete descent into Agambenian bare life, so this article enriches our understanding of how the homo sacer concept operates empirically.